Improving Students' Concept Understanding of Lens Refraction Material by Using STEM-Based E-Modules: A Feasibility Test - Nia Fitrotul Masulah; Japung Wiraputra; Bayu Setiaji (Universitas Lambung Mangkurat, 2023)
This study aims to test the feasibility level of learning media in the form of STEM-based electronic modules on refraction material in lenses to improve the conceptual understanding of SMA / MA students. The research method used is R & D using the 4D model (Define, Design, Develop, and Disseminate). However, this research only reached the development stage by testing the feasibility of e-modules. STEM-based e-modules on lens refraction material are presented as online flipbooks so that their use can be accessed via smartphones (android or iOS). Data collection in this study was carried out by distributing feasibility test questionnaires to 3 validators consisting of 2 Physics Education expert lecturers who have taught for 1 and 2 years, 1 physics teacher who has taught for 25 years, and 53 prospective physics teachers. Based on the feasibility test results by the validator, the STEM-based e-module to improve students' conceptual understanding of lens refraction material is in the category suitable for use in learning. The implication is that because the e-module has been declared feasible in the development process, the e-module can be implemented in physics learning to increase students' conceptual understanding of the concept of refraction.